Fs Laser‐Induced Plasmas from Energetic Polymers: Towards Micro‐Laser Plasma Thruster Application. Issue 6 (24th November 2015) - Palla Papavlu, Alexandra; Urech, Lukas; Lippert, Thomas; Phipps, Claude; Hermann, Jörg; Wokaun, Alexander
Abstract : The micro‐laser plasma thruster (μ‐LPT) is a device aimed at orienting and repositioning small satellites above the atmosphere. These devices are based on IR diode lasers utilized for the ablation of polymers and production of thrust for the control of the satellite motion. In this work, different polymer systems, i.e., poly(vinyl chloride) (PVC), glycidyl azide polymer (GAP), and poly(vinyl nitrate) (PVN) with two absorbers, i.e., carbon nanoparticles (C) and an IR‐dye (IR), have been investigated for an application in μ‐LPT. The properties of a plasma produced by the irradiation of GAP + C, GAP + IR, PVC + C, and PVN + C with 100 fs laser pulses has been investigated by time‐resolved plasma imaging and time and space resolved plasma emission spectroscopy. Abstract : This study is the first investigation of a plasma produced by fs irradiation of different fuel polymers (PVC, GAP, and PVN) doped with absorbers (carbon nanoparticles and IR‐dye). By applying plasma imaging and plasma emission spectroscopy, the propagation velocities of selected plasma species have been determined, which are particularly important for applications in micro laser plasma thrusters.